CYBERFEMINIS SEBAGAI BENTUK BARU PERGERAKAN PEREMPUAN DI ERA DIGITAL: Pada Akun Instagram Plainfeminism - Will Chinyere, (2021)
In the era of digital, every individual or groups must require themselves to interact actively with new media. New media can be used to broadly convey the vision and mission. Feminist groups can convey their ideas through new media because new media offer an idea of women's liberation. With a combination of feminism and technology (new media), its adherents are called cyber-feminists. In Indonesia, there is an Instagram account that focuses on basic feminism education. Researcher intends to examine more deeply the reasons for cyberfeminists to form a feminist Instagram account and how this account is used to remove stereotypes on women. Researcher using qualitative descriptive, data obtained through interviews, acount observations, and looking at supporting data. From the results of this study, it is known that the reason is to fight patriarchal culture, fight negative feminism views, and also provide a means of communication for cyberfeminists. This account is used to discuss and form a community.